2021
DOI: 10.1172/jci.insight.147282
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between nonclassical monocytes and alveolar macrophages mediates transplant ischemia-reperfusion injury through classical monocyte recruitment

Abstract: Primary Graft Dysfunction (PGD) is the predominant cause of early graft loss following lung transplantation. We recently demonstrated that donor pulmonary intravascular non-classical monocytes (NCM) initiate neutrophil recruitment. Simultaneously, host-origin classical monocytes (CM) permeabilize the vascular endothelium to allow neutrophil extravasation necessary for PGD. Here, we show that a CCL2-CCR2 axis is necessary for CM recruitment. Surprisingly, although intravital imaging and multichannel flowcytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 63 publications
(102 reference statements)
1
51
0
Order By: Relevance
“…We have recently reported that AM produce CCL2 after lung transplantation ( 25 ). TGF-β targets activation of AP-1 and EGR1, transcription factors that can promote CCL2 gene transcription ( 47, 48 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that AM produce CCL2 after lung transplantation ( 25 ). TGF-β targets activation of AP-1 and EGR1, transcription factors that can promote CCL2 gene transcription ( 47, 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports show that Mo-AM are derived from bone marrow-derived cells, but have not directly addressed whether this AM subset arises from CCR2 + monocytes ( 22, 23 ). CCR2 expression on monocytes is critical for trafficking into inflamed lungs in response to the chemokine CCL2 ( 24, 25 ). CCR2 expression and Mo-AM have been shown to drive bleomycin-induced pulmonary fibrosis raising the possibility that CCR2 + monocytes drive pulmonary fibrotic disease through differentiation into Mo-AM ( 21, 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 Retained donor pulmonary intravascular nonclassical monocytes initiate recipient neutrophil recruitment to donor graft following transplantation, playing a central role in development of acute lung injury. 33,34 Furthermore, preimplantation classical donor monocyte numbers have been correlated…”
Section: Discussionmentioning
confidence: 99%
“…As the development of single-cell sequencing technologies, scRNA-seq has been gradually applied to study immune cells and immune responses in mouse lungs (Ballesteros et al, 2020;Cohen et al, 2018;Kurihara et al, 2021;Wang et al, 2021). In many cases, T helper cells and cytotoxic T cells can be identified in these scRNA-seq studies, but not their subtypes.…”
Section: Discussionmentioning
confidence: 99%